Anti‐B lymphocyte immunotherapy is associated with improvement of periodontal status in subjects with rheumatoid arthritis. (8th September 2015) - Coat, Juliette; Demoersman, Julien; Beuzit, Sébastien; Cornec, Divi; Devauchelle‐Pensec, Valérie; Saraux, Alain; Pers, Jacques‐Olivier
Abstract Aim Rheumatoid arthritis (RA) and periodontitis present many similar features. The benefits of anti‐B lymphocyte therapy (rituximab) on reducing tissue resorption in RA prompted us to assess its potential efficacy on the periodontal status of patients with RA treated with rituximab. Materials and Methods Periodontal status was assessed in 21 subjects with RA, divided into two groups: Group I consisted in 11 subjects assessed before their first infusion of rituximab and again 6 months later. Five of them were also assessed for up to 4 years after their first rituximab infusion. The 10 subjects in group II had received more than two courses of two rituximab infusions at the time of periodontal assessment. Results Pocket depth and attachment loss were significantly decreased 6 months after treatment with rituximab in group I. The periodontal status of the five subjects from group I followed for up to 48 months after rituximab treatment was improved irrespective of the clinical parameter observed. Patients from group II had a better periodontal status than patients from group I before treatment with rituximab. Conclusions Anti‐B lymphocyte therapy could be beneficial to improve periodontitis suggesting a major role of B cells in this disease.